A New Panorama of Wound Healing: A Review on Advances in Wound Healing Formulations - Ashwani Mishra; Subhash Pande; Anupam Pathak (Current Research in Pharmaceutical Sciences, 2014)
From a divine creation to a massive complex system, this human body has slowly and steadily becomes less mysterious to us. With the up gradation, sophistication, and modernization of civilisation and technology and continuously changing teachings, and methodology, massively changed the care of both acute and chronic wounds. This article provides an overview of some of the methods employed and some are being used by physicians to enhance the wound healing process. The plurality of wound from Necrotic to malodorous have resulted in a wide range of wound dressings. If we try to define ideal dressing than it should achieve rapid healing at reasonable cost with minimal inconvenience better compatibility and feasibility to the patient. An attempt is made to write a review of the advances wound management dressings, emerging technologies for achieving improved wound healing, novel polymers used for the delivery of drugs to acute, chronic and other types of wound and It also reviews many of the dressings include adherent, non adherent, film dressing ,polysaccharides used in dressing, chitosan, alginates, hydrogel ,Foam dressing .Silicon dressing, deodorize, collagen and Larvae therapy. This review also concerns the requirement for formulations towards achieving optimum physical properties and desired characteristics for an active wound healing dosage form briefly.